Novel toxin genes, biological activity of putative toxins and molecular phylogeny of Conus furvus Reeve, 1843 - Espino, Samuel S. (2006)
The genus Conus comprises a remarkable group of predatory marine gastropods characterized by a special biochemistry of small constrained peptides, the conotoxins. These conotoxins have an extremely high affinity to a particular ion channel in the snail's prey. In this research, conotoxins from Conus furvus were deduced from cDNA sequences. Conotoxins of the O- and the M - superfamily were obtained. The O-superfamily conotoxin has the sequence SCTPRGGQCGYYNDCCSHQCNINRNLCE and the M - superfamily conotoxin has the sequence RCCKFPCANSCRHLCCG. The M - superfamily conotoxin has a high degree of identity and similarity with conotoxins expressed by the mollusc hunting snails Conus textile and Conus marmoreus. HPLC fractions obtained from the snail's venom show activities ranging from sluggish and sleep - like behavior to hyperactivity and convulsion in mice. Phylogenetic analyses utilizing several mithochondrial DNA sequences indicate that C. furvus preys on molluscs.